Barriers and challenges faced in the Swedish defense industry Mitigation by business model component modification - Edeland, Hampus; Burrill, Robin (My University, 2024)
The Swedish defense industry is dominated by a handful of suppliers, raising the question of why smaller suppliers find it hard to compete. This thesis investigates the barriers and challenges faced by smaller suppliers in the Swedish defense industry. Furthermore, the thesis examines how these suppliers can mitigate these barriers and challenges by modifying their business model, particularly in terms of key resources, partnerships, customer relationships, and channels. The thesis explores theoretical data regarding business model components and the barriers and challenges within the defense industry. Qualitative methods were also applied through semi-structured interviews with both large and small Swedish defense suppliers. The findings reveal significant challenges in procurement processes, primarily due to stringent requirements and complex specifications that impact smaller suppliers to a greater extent. Key factors such as industry know-how and contacts prove crucial in providing market access in the intricate defense industry environment. The research identifies a need for more streamlined procurement processes and eased supplier requirements that could enable greater participation from smaller entities and enhance innovation within the Swedish defense industry. This study contributes to a better understanding of the dynamics in defense procurement and suggests modifications to business models that could mitigate existing barriers, thereby fostering greater competitiveness for smaller suppliers.
Keywords: Barriers; Business Model; Challenges; Procurement; Smaller Supplier; Swedish Defense Industry.